Ensino dos pontos notáveis do triângulo com auxílio do GeoGebra - Vignatti, Luciano (2016)
In this work we present two experiences in teaching triangle centers to eighth grade students. One was done using the traditional method, through the use of expository lessons, while the other was done through the use of the software GeoGebra. We also present some theorems about triangle centers, as well as activities with GeoGebra for the teaching of this subject